Perancangan Interior Souvenir Shop Berbasis Human Centered Design Di Ekowisata Mangrove Surabaya - Melissa Oka; mariana wibowo; filipus priyo suprobo (Intra, 2015)
The design of commercial facilities in the form of a souvenir shop in Mangrove Ecotourism Surabaya is designed to support Surabaya city’s government and also the Wonorejo Ecotourism institution in developing the facilities at Mangrove ecotourism wonorejo in order to fulfill the tourist’s needs of particular handicrafts sale of mangrove ecotourism Surabaya and having the education value of mangrove processed goods. The souvenir shop consists of storage room, cashier area, and display area. The design process based on Human Centered Design. The concept used in this design is fusing the 2 concepts of Mangrove ecoutourism surabaya, which are eco-friendly and the concept of Griya Karya Tiara Kusuma’s storytelling waste recycle, resulting in the usage of the word “identity”. The concept of “identity” will be applied in three themes or interior-exterior ambience, which are indonesian style, boat, and tree. Aside from the ambience, “identity” will also be applied on furniture that adjust each of their identities. The style used in the concept “identity” is vernacular. The result creates a traditional ambience that compliment the surrounding condition of mangrove ecotourism surabaya, so the tourist’s need of souvenir shop facility is fulfilled.